Effects of computer-assisted instruction on the learning of quadratic curves by secondary two students - Yeo, Joseph Kai Kow. (2009)
This study sets out to investigate the effects of two modes of instruction on the learning of quadratic curves among the secondary two students. The two modes of instruction are Computer-Assisted Instruction (CAI) and Traditional Approach (TA). These two approaches were examined in terms of their effects on achievement and attitudes, both toward the topic and the subject. A total of 192 students from the Express stream of an independent school in Singapore participated in the study.